Sinergitas akademi dan masyarakat dalam membangun Desa: kolaborasi mahasiswa bersama masyarakat dalam meningkatkan pembangunan di Dukuh Tilaman - Nufus, Saodiatin; Nugraheni, Anja Rossa Eka Putri Chenita; Salsabila, Shafa; Nasrudin, Muhamad (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
The Real Work Lecture was held in Padukuhan Tilaman, Wukirsari Village, Imogiri District, Bantul Regency, Yogyakarta Special Region Province. For 4 weeks and 3 days starting from 05 February to 06 March 2024. Padukuhan Tilaman is the padukuhan chosen to be the padukuhan for KKN purposes by group 5 from Cokroaminoto University Yogyakarta. The abundant village potential is one of the main objectives of implementing KKN to improve the quality of Human Resources (HR) in processing and developing the potential of local villages. KKN begins with a village observation process to see the potential of villages that will be targets in implementing KKN. The programs are designed sequentially starting with discussions between KKN groups, village officials and local communities, especially those that have direct contact with the programs being designed. The implementation of the KKN program is carried out in a balanced manner starting with planning, implementation and evaluation at the end of each program. The results achieved from the entire KKN program include developing community skills and helping develop Human Resources (HR) to increase the potential of local villages. In the field of education, namely tutoring programs both academically and religiously based, are implemented to develop quality human resources from an early age. Apart from that, in the religious sector, namely the empowerment of mosques and TPAs. In the environmental sector, making a plan of Tilaman hamlet. In the legal field, namely the dissemination of hoax news to the local community. In the economic sector, namely socialization about how to save and socialization of digital marketing to local MSMEs in Tilaman Hamlet, Imogiri District, Bantul Regency, Yogyakarta Special Region Province.